Does Communication Effectiveness Assessed by Communication Scholars Correlate with Patient Perception of Clinician Empathy? - Haley Ponce BS; Rafael Cordero BS; Jacinta Tran BS; Natalie Wellman BS; David Ring BS (Journal of Patient Experience)
In a prior study, communication scholar ratings of clinician communication effectiveness did not correlate with perceived clinician empathy, which is one aspect of patient experience. We repeated the analysis with a different rating of communication effectiveness to increase confidence that the lack of association was not due to an inadequate rating tool. Video-recorded visits (108) were rated by 3 trained observers using the Communication Quality Analysis with acceptable reliability. Patients completed measures of perceived clinician empathy, pain accommodation, health anxiety, and depression symptoms. Negative binomial regression analysis sought factors associated with perceived clinician empathy. Only accommodation of pain met the criterion for entry into a multivariable model for perceived clinician empathy (ρ = 0.17; P  = .08). No factors were associated with perceived clinician empathy, including independently rated communication effectiveness. The consistent finding of no correlation between communication effectiveness and patient perception clinician empathy using a second rating tool does not diminish the importance of effective patient–clinician communication, but it does reinforce the need to identify suitable measures of modifiable factors associated with poor patient experience.